Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Rapid assembly of structurally diverse 3,4-dihydroquinazolines with anticancer activity via SDS-promoted aqueous synthesis - Fu-Qiang Yu; Pei-Lu Song; Yan-Rui Fan; Jun-Wei Wang; Xu-Jie Wang; Jin-Fei Yang (Molecular Diversity, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Vitamin C mitigates early auditory cortical hyperexcitability and antioxidant imbalance induced by acute intermittent hypoxia - Yue Wu; Tao Li; Wanxin Cao; Rui Fan; Hailing Jiang; Jiachen Han; Furong Ma; Yan Yan (Experimental Brain Research, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Accelerating Sugarcane Breeding with Machine Learning: A Concurrent Multi-trait Predictive Approach - Haichuan Fan; Jing Chao; Xiaoyan Liu; Pengcheng Ma; Guanghu Zhu; Ming Li; Rui Yan; Xinyi Li; Yan Jing; Fengbing Li; Ting Luo; Prakash Lakshmanan (Sugar Tech, 2026)
A large and highly polyploid genome, long breeding cycles, low narrow-sense heritability of yield and its components, and persisting yield stagnation continue to challenge sugarcane variety improvement through both conventional and molecular breedings. To address this, this study developed an efficient phenotype-based concurrent multi-trait prediction framework using artificial intelligence, leveraging 2700 parent combinations and their offspring field performance data from the Sugarcane Research Institute of Guangxi Academy of Agricultural Sciences. Five machine learning paradigms were selected based on data characteristics: tree-based models (GBDT, XGBoost) for structured tabular data and nonlinear trait interactions; attention-based tabular models (TabTransformer, TabNet) for subtle cross-trait dependencies; and an MLP as a baseline. All models were optimized via 80/20 stratified train–test split, class-weighted loss, and cross-validated grid search. GBDT achieved the best overall performance with a macro F 1 score of 0.7316, Hamming loss of 0.2052, and sample accuracy of 0.5630, excelling in predicting sucrose content, cane yield, and smut resistance. XGBoost performed comparably, while TabTransformer offered complementary advantages with a higher F 1 score (0.6829) on overall agronomic performance. These results indicate the potential of using artificial intelligence (AI), particularly machine learning (ML), to increase the predictive power and robustness through integrated AI approaches in the future. This phenotype-based framework shows the value of ML as an efficient decision support tool that can help breeders prioritize cross combinations and optimize resource use, thereby reducing reliance on extensive field trials. While the potential of AI in accelerating variety development is evident, its routine application in real-world commercial breeding requires validation.

Research on Environmental Response Characteristic of Super-Long Inclined Shaft Tunnel and CO Diffusion and Ventilation Optimization of Blasting Procedures - Kong-fei Yu; Huai-bing Wang; Hong-yan Wang; Chen-qi Fan; Bu-rui Liu; Xuan-ke Ren (Applied Geophysics, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Sodium-glucose cotransporter 2 inhibitors and contrast-induced nephropathy risk: a meta-analysis - Gang Fan; Lin Lin; Hong Zuo; Rui Yan; Chao Xu (European Journal of Clinical Pharmacology, 2025)

Prediction of sandstone porosity in coal seam roof based on variable mode decomposition and random forest method - Ya-ping Huang; Xue-mei Qi; Yan Cheng; Ling-ling Zhou; Jia-hao Yan; Fan-rui Huang (Applied Geophysics, 2025)

Microglia programmed cell death in neurodegenerative diseases and CNS injury - Ling Cai; Qiuyue Fan; Rui Pang; Chen Chen; Yueman Zhang; Haiyi Xie; Jingyi Huang; Yu Wang; Peiying Li; Dan Huang; Xia Jin; Yuxi Zhou; et al. (Apoptosis, 2025)

Changing Drip Fertigation Strategy to Decrease Greenhouse Agroecosystem Soil Nitrate Residue and Improve Tomato Production in Northwest of China - You Wu; Jiale Zhang; Shicheng Yan; Wei Si; Rui Liu; Jianhua Yang; Zhenxin Qiu; Junliang Fan; Fucang Zhang (Journal of Soil Science and Plant Nutrition, 2024)

Isolation, identification and transcriptome analysis of triadimefon-degrading strain Enterobacter hormaechei TY18 - Yan Wang; Qi Guan; Wenhui Jiao; Jiangbo Li; Rui Zhao; Xiqian Zhang; Weixin Fan; Chunwei Wang (Biodegradation, 2024)

Effect of exogenous Ca on the physiology and growth indicators of pakchoi under foliar and root fluorine stress - Rui Liu; Si-fan Cui; Chun-dan Gan; Jin-yan Yang (Environmental Geochemistry and Health, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

Genome-wide identification of black pepper (Piper nigrum L.) Dof gene family and the differential gene screening in resistance to Phytophthora capsici - Fenju Zhang; Rui Fan; Lin Yan; Lisong Hu; Fan Su; Dewei Yang; Jing Li (Biologia, 2022)

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Association between glucagon-like peptide-1 receptor gene polymorphism and treatment response to GLP1R agonists in Chinese patients with type 2 diabetes: a prospective cohort study - Ziwan Guan; Yue Du; Rui Li; Shufang Zhang; Yuedong Xu; Xiaoqian Zhang; Fan Zhang; Ying Yin; Kunrong Wu; Xiaoli Li; Yan Li (European Journal of Clinical Pharmacology, 2022)

Gisenoside Rg1 attenuates cadmium-induced neurotoxicity in vitro and in vivo by attenuating oxidative stress and inflammation - Teng-Teng Ren; Jia-Ying Yang; Jun Wang; Sheng-Rui Fan; Rongfeng Lan; Xiao-Yan Qin (Inflammation Research, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

Stress analysis of subsea risers under the combined action of wave force and seismic wave - Dongfeng Li; Shangyu Yang; Heng Fan; Rui Wang; Xiangzhen Yan (Arabian Journal of Geosciences, 2021)

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

Psychroflexus maritimus sp. nov., isolated from coastal sediment - Yan-Lin Zhong; Rui Zhang; Xiao-Yu Zhang; Li-Xue Yu; Meng-Fan Zhao; Zong-Jun Du (Archives of Microbiology, 2020)

The Role of 17β-Estrogen in Candida albicans Adhesion on Human Vaginal Epithelial Cells via FAK Phosphorylation - Ting Luan; Xia Liu; Pengyuan Mao; Xinyan Wang; Can Rui; Lina Yan; Yiquan Wang; Chong Fan; Ping Li; Xin Zeng (Mycopathologia, 2020)

Rapid and efficient removal of naproxen from water by CuFe2O4 with peroxymonosulfate - Rui Bai; Yong Xiao; Weifu Yan; Siqi Wang; Rui Ding; Fan Yang; Junpeng Li; Xiaoquan Lu; Feng Zhao (Environmental Science and Pollution Research, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Evaluation of Inoculum Sources for Aerobic Treatment of 2,3,4-Trifluoroaniline During Start-up and Shock - Zhi-Qing Zhao; Xiao-Li Shen; Tu-Cai Zheng; Ghulam Abbas; Rui Fan; Yan-Mei Li (Water, Air, & Soil Pollution, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Effects of resveratrol on regulation on UCP2 and cardiac function in diabetic rats - Jiayu Diao; Jin Wei; Rui Yan; Gang Fan; Lin Lin; Mengjie Chen (Journal of Physiology and Biochemistry, 2019)

RNA Sequence Analysis of Cassava Varieties with High-Starch Content Using De Novo Assembly - Ya-Jing Guo; Xing-Lu Luo; Mao-Gui Wei; Zhao-Liang Liu; Wu-Jing Fan; Rui-Ning Zhai; Yan-Mei Zhu (Journal of Plant Growth Regulation, 2018)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Ne2 encodes protein(s) and the altered RuBisCO could be the proteomics leader of hybrid necrosis in wheat (Triticum aestivum L.) - Si Rui Pan; Xing Lai Pan; Qian Ying Pan; Yin Hong Shi; Li Zhang; Yun Fan; Yan Rui Xue (Journal of Genetics, 2017)

Blood Flow and Oxygen Transport in Descending Branch of Lateral Femoral Circumflex Arteries After Transfemoral Amputation: A Numerical Study - Fei Yan; Wen-Tao Jiang; Rui-Qi Dong; Qing-Yuan Wang; Yu-Bo Fan; Ming Zhang (Journal of Medical and Biological Engineering, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

A Novel Chromone Schiff-Base Fluorescent Chemosensor for Cd(II) Based on C=N Isomerization - Jun Yan; Long Fan; Jing-can Qin; Chao-rui Li; Zheng-yin Yang (Journal of Fluorescence, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

A Chromone-Derived Schiff-Base Ligand as Al3+ “Turn on” Fluorescent Sensor: Synthesis and Spectroscopic Properties - Chao-rui Li; Jing-can Qin; Bao-dui Wang; Long Fan; Jun Yan; Zheng-yin Yang (Journal of Fluorescence, 2016)

Cloning and Functional Analysis of Thylakoidal Ascorbate Peroxidase (TAPX) Gene in Sugarcane - Sheng Wang; Kun-Kun Zhang; Xing Huang; Yan-Jiao Fan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Screening of Inherited Metabolic Disorders in Infants with Infantile Spasms - Xiao-Ming Liu; Rui Li; Sheng-Zhi Chen; Yan Sang; Jiao Chen; Cong-Hai Fan (Cell Biochemistry and Biophysics, 2015)

Trichoderma biodiversity in China - Rui-yan Sun; Zhi-cheng Liu; Kehe Fu; Lili Fan; Jie Chen (Journal of Applied Genetics, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

Synthesis of benzopyrano[4,3-b](N-arylsulfonyl)indoles and benzopyrano[3,4-b](N-arylsulfonyl)indoles via intramolecular palladium-catalyzed aryl–aryl coupling reaction - Ling-ling Fan; Zhi-ping Che; Rui Zhang; Xiang Yu; Xiao-yan Zhi; Hui Xu (Molecular Diversity, 2012)

Proteomic analysis of seed germination under salt stress in soybeans - Xiao-yan Xu; Rui Fan; Rui Zheng; Chun-mei Li; De-yue Yu (Journal of Zhejiang University-SCIENCE B, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)